PENILAIAN KINERJA DENGAN MENERAPKAN INDIKATOR VALUE FOR MONEY PADA KANTOR PERTANAHAN KABUPATEN MUSI BANYUASIN TAHUN 2009 – 2011 - IKA SASTI FERINA; FIKA ARISTA (Program Studi Magister Manajemen FE Unsri, 2013)
This research was conducted to assess the performance of Kantor Pertanahan Kabupaten Musi Banyuasin in doing their operational activity economically, efficiency, and effectively that was analyzed by indicator of value for money. The data used in this study was financial and other supporting data in the period from 2009 to 2011. The results showed Kantor Pertanahan Kabupaten Musi Banyuasin was stated inefficient in 2009 and 2010, but otherwise stated economic and effective in the year 2009 to 2011. This research also found that there were some damage of office equipments and vacant position in the Kantor Pertanahan Kabupaten Musi Banyuasin.